Diastase Enzyme Activity and Antibacterial Effectiveness to Gastroenteretis by Apis mellifera Honey from Indonesia - Rosyidah, Rara Annisaur; Hasan, Akhmad Endang Zainal; Andrianto, Dimas (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
The quality of monoflora honey (Apis mellifera) as an antibacterial can be influenced by the activity of the diastase enzyme and the secondary metabolites of the nectar source. This study aims to compare the activity of the diastase enzyme and the effectiveness of monoflora honey derived from Apis mellifera bees as a natural antibacterial agent against Salmonella typhi. The sampling method for monoflora honey from nine different nectar sources (acacia, calliandra, rambutan, eucalyptus, randu, mango, robusta coffee 1, robusta coffee 2, and rubber). The results showed that the highest diastase enzyme activity in monoflora honey was mango, rambutan, and robusta coffee 2 at 20.00 DN, eucalyptus, randu, and rubber at 10.00 DN, acacia at 6.67 DN, robusta coffee 1 5.00 DN, and calliandra 4.00 DN. Zone of inhibition for S. typhi on robusta coffee 2, robusta coffee 1, randu, eucalyptus, acacia, mango, rubber, rambutan, and calliandra respectively at 18.53; 16.70; 15.27; 14.70; 13.20; 11.20; 11.17; 9.47; and 6,80. The minimum concentration inhibition was 8 μg/mL.